Student Egocentric Control through the Student Team Achievement Division Design - Fathor Rozi; Aminulloh Aminulloh; Hasan Baharun; Asmawati Asmawati; Fathatun Hasanah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to find out how to apply the STAD cooperative learning model as an effort to control the egocentricity of early age students (5-7 years). This research uses a qualitative approach with a case study type. The research location was in Raudhatul Athfal Khoiriyah, Bulang Village, Gending District and the research subjects were conducted in class B students. The data collection techniques used were observation, interviews with 4 informants, namely the principal, and two class teachers, and documentation. The data analysis model with the interactive analysis model from Miles and Huberman includes the steps of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Student Teams-Achievement Divisions (STAD) learning model is able to control student egocentricity in group work for making mini wall magazine. The teacher's efforts in applying the STAD model are by presenting information, goals and motivation, organizing students into heterogeneous groups, evaluating learning outcomes, and giving awards to students. This is what makes the STAD learning model able to make student learning concepts active, free to be creative, free from narcissism-individualism, active in interactions, and active in respecting each individual opinion in class.